The Next Step for Transport in the SDGs : Devising the Right Indicators Shaping Transport’s SDG Impact - Ensink, Bernhard; Minovi, Shokraneh; Gorham, Roger; Vandycke, Nancy (World Bank, Washington, DC, 2016)
Transport was not part of the millennium development goals (MDGs) for 2000-15, which were adopted at the United Nations in September 2000. The omission was widely viewed in the transport community as a missed opportunity to use the strong linkage between transport and economic development to advance the attainment of the MDGs. Now a new 15-year development framework, the sustainable development goals (SDGs) for 2015-30, are about to be endorsed at the United Nations summit to be held September 25-27, 2015. This time, transport will be part of the framework as a key contributor to sustainable development. The SDGs comprise 17 goals and 169 targets; five of those targets directly involve transport, and attaining at least another six will critically depend on it. But efforts to influence the post-2015 development agenda will go on after the summit because the question of what indicators will be used to measure success is yet to be resolved. Attention in the transport community must now pivot toward that question to assure the selection of the most effective measures.